A metabolic, phylogenomic and environmental atlas of diatom plastid transporters from the model species Phaeodactylum - Liu, Shun; Storti, Mattia; Finazzi, Giovanni; Bowler, Chris; Dorrell, Richard G. (Frontiers in Plant Science, 2022)
Diatoms are an important group of algae, contributing nearly 40% of total marine photosynthetic activity. However, the specific molecular agents and transporters underpinning the metabolic efficiency of the diatom plastid remain to be revealed. We performed in silico analyses of 70 predicted plastid transporters identified by genome-wide searches of Phaeodactylum tricornutum. We considered similarity with Arabidopsis thaliana plastid transporters, transcriptional co-regulation with genes encoding core plastid metabolic pathways and with genes encoded in the mitochondrial genomes, inferred evolutionary histories using single-gene phylogeny, and environmental expression trends using Tara Oceans meta-transcriptomics and meta-genomes data. Our data reveals diatoms conserve some of the ion, nucleotide and sugar plastid transporters associated with plants, but also possess unique transporters with different substrates and localization patterns. These confirm previous observations that substrate non-specific triose phosphate transporters (TPT) may exist as principal transporters of phosphorylated sugars into and out of the diatom plastid, alongside suggesting probable agents of NTP exchange. Carbon and amino acid transport may be related to intricate metabolic plastid-mitochondria crosstalk. We additionally provide evidence from environmental meta-transcriptomic/meta- genomic data that plastid transporters may underpin diatom sensitivity to ocean warming, and identify a diatom plastid transporter (J43171) whose expression is positively correlated with temperature.